miR-29a-3p/T-bet Regulatory Circuit Is Altered in T Cells of Patients With Hashimoto’s Thyroiditis - Tokić, Stana; Štefanić, Mario; Glavaš-Obrovac, Ljubica; Kishore, Amit; Navratilova, Zdenka; Petrek, Martin (Frontiers in Endocrinology, 2018)
Objective: Hashimoto’s thyroiditis (HT) is a common autoimmune thyroid disorder that frequently evolves from asymptomatic, T-cell mediated chronic inflammation towards overt hypothyroidism. Previously, we have demonstrated a role for T-bet, a T helper 1/CD8+ T cell transcription factor (TF), and FoxP3, a regulatory T cell TF, in disease progression and severity, but the basis behind their altered mRNA expression remains unknown. In the current study, we aimed to leverage the role for microRNAs, representing negative transcriptional regulators, across the spectrum of HT clinical presentations using the same, well-characterized RNA sample cohort. Method: Ten hypothyroid, untreated patients (hypoHT), 10 hypothyroid cases rendered euthyroid by L-thyroxine therapy (substHT), 11 spontaneously euthyroid HT subjects (euHT) and 10 healthy controls (ctrl) were probed for three candidate immunoregulatory miRNA (miR-9-5p, miR-29a-3p and miR-210-3p) using qRT-PCR measurements. Data were normalized to U6snRNA and fold difference in expression calculated by the efficiency corrected 2-ΔΔCt model. Results: Compared to healthy controls, peripheral blood (PB) T cells of HT patients exhibited significantly diminished miR-29a-3p expression levels [median expression levels (IQR), HT vs CTRL, 0.62 (0.44-1.01) vs 1.373 (0.63-2.7), P=0.046], and a similar, but not significant decline in miR-210-3p abundance [HT vs CTRL, 0.64 (0.39-1.31) vs 1.2 (0.5-2.56), P=0.24, Wilcoxon test]. A significant inverse correlation was observed between the two differentially expressed transcripts, T-bet mRNA and miR-29a-3p. Moreover, altered miR-29a-3p/T-bet expression in T cells of untreated HT patients was related to low serum FT4, high serum thyrotropin and decreased thyroid volumes. Of note, miR-210-3p expression was positively correlated to HIF1α, and inversely to FoxP3 mRNA levels, but no evidence of differential expression for any of these miRNA-mRNA pairs was observed. Finally, miR-9-5p expression levels were no different in HT versus control comparisons, or related to clinicopathological features. Conclusions: T cell miR-29a-3p is down-regulated in HT patients and associated with clinical and biochemical parameters of progressive thyroid injury, plausibly subsequent to altered control of T-bet expression in peripheral blood T cells. As such miR-29a-3p/T-bet axis should be further explored as a biomarker or as a plausible target for therapeutic interventions in HT.